Ocorrência de C. tropicalis no Hospital Universitário Cassiano Antônio de Moraes, estudo de sua suscetibilidade a antifúngicos com propostas de métodos modificados para aprimoramento dos testes in vitro - Malacarne, Bruna (2010)
The frequency of candidemia has increased in recent decades, with raising occurrence of non-albicans species. In general, Candida tropicalis is the most frequent non-albicans species in Brazil and may present trailing growth in broth microdilution tests with azole drugs, which complicates and confuses the reading of MIC values. The objectives of this study were evaluate the occurrence of candidemia caused by C. tropicalis in HUCAM and your susceptibility profile with fluconazole, itraconazole and amphotericin B, according to reference methodology M27-A3 (CLSI, 2008) propose modifications in this test, and evaluate the influence of different incubation periods and ways of reading. Isolates of Candida tropicalis were selected and submitted to the modified tests: incubation temperature of 42°C, addition of TSA and colorimetric compound resazurin. The results obtained with modified tests were evaluated through essential and categorical agreements considering the reference methodology. The results showed that in the period of 2006 to 2009, the frequency of candidemia in HUCAM ranged from 1.21 to 1.65 cases / 1,000 admissions and 0.16 to 0.25 cases / 1,000 patient-days. C. albicans accounted for 45% of the episodes, followed by C. tropicalis (26%), C. parapsilosis (14%), C. glabrata (10%) and other ones (C. krusei, C. guilliermondii and C. lusitaniae). The highest percentages of resistance to fluconazole and itraconazole occurred with 48 hours of incubation (26% versus 5% and 17% versus 1.2%, respectively). 28.05% of the isolates showed trailing growth for one or both drugs. The categorical and essential agreements of the modified tests when compared with the standard methodology, ranged from 70 to 87%, with 24 hours of incubation and for both drugs. With 48 hours of incubation, the modifications (incubation at 42°C and addition of TSA) provided smaller percentages of categorical and essential agreements when compared with the addition of resazurin. The best agreement between ways of reading (visual and spectrophotometric) was obtained with the incubation at 42°C, compared with the standard method. Different trailing growth profiles were observed and the three modified methods were effective in reducing this phenomenon with 24 hours of incubation, but only the methods 42°C and TSA were able to reduce it at 48 hour. The analysis of medical records indicated that isolated with trailing growth showed 11 satisfactory therapeutic response to fluconazole and the isolated that remained resistant in the modified tests did not respond to treatment with fluconazole in vivo